Optimising The Human Resource Potential Of University Education Personnel: Recruitment, Training, Welfare, And Performance Evaluation Strategies To Improve Effectiveness And Productivity - Santanu, Tita Rachtawati; Paroli, Paroli; Atmaja, Hanung Eka; Nadzari, Suhaila Binti (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objective: Improving the quality of human resources (HR) of education personnel is crucial to supporting an effective and productive higher education system. This study aims to analyze the effect of recruitment, Training, welfare, and performance evaluation on the effectiveness and productivity of education personnel in Garut Regency universities.Methodology: This study uses a quantitative approach with descriptive and causal designs. The population consisted of all education personnel in Garut Regency universities, with a sample of 271 respondents selected through a purposive sampling technique. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression using SPSS software.Findings: The results showed that recruitment, Training, and performance evaluation positively and significantly affect the effectiveness and productivity of higher education personnel. These three factors are key in improving performance through HR planning, competency development, and performance-based evaluation. Meanwhile, welfare does not show a significant effect, indicating that structural and managerial factors are more decisive than material in resource-limited universities such as the Garut Regency. This finding confirms the importance of strategic HR governance in supporting higher education quality improvement.Conclusion: These results confirm that HR management strategies that focus on competency-based recruitment, relevant Training, and structured performance evaluation are critical to improving the effectiveness and productivity of education personnel, especially in resource-constrained regions. The practical implication is that universities in areas such as Garut must prioritize the capacity building of education personnel through contextual and sustainable HR management policies.